Implementation of Problem Based Learning Model to Enhance Learning Outcome on Fiqh Muamalah Concepts in Sharia Banking and Sharia Cooperatives in Class X SMK Cendikia Paseh - Firmansyah, Firmansyah; Muhamadi, Sani Insan (Al-Aulad: Journal of Islamic Primary Education, 2023)
This study aims to enhance understanding of Fiqh Muamalah concepts in Sharia banking and Sharia cooperatives through the implementation of the Problem-Based Learning (PBL) model in Class X at SMK Cendikia Paseh. Classroom Action Research (CAR) method is employed. Results indicate significant improvement in student learning outcomes, particularly during group and class discussions. Students exhibit increased enthusiasm and active participation in learning activities. Understanding among students during group and class discussions increased from 70% (14 students) in Cycle 1 to 85% (17 students) in Cycle 2, representing a 15% improvement. Thus, it can be concluded that the implementation of the Problem-Based Learning model effectively enhances understanding of Islamic Education in Sharia banking among Class X students at SMK Cendikia Paseh for the academic year 2023/2024.